Kurikulum Cinta sebagai Paradigma Penguatan Moderasi Beragama dalam Pengembangan Kurikulum Pendidikan Agama Islam di Madrasah - Sukmayeti, Sukmayeti; Masnita, Delmi; Hamidar, Nur; Fauzi, Muhammad; Wahyuni, Sri (Lembaga Yasin AlSys, 2026)
Kurikulum Cinta is a new approach in Islamic education that places the values of compassion, humanity, and peace at the core of learning, while also serving as a response to contemporary religious challenges such as intolerance, exclusivism, and tendencies toward extremism that risk reducing the meaning of religious education. This article aims to examine in depth the theoretical foundations of Kurikulum Cinta and its implementation in strengthening religious moderation through the development of the Islamic Religious Education curriculum in madrasah. This study employed a qualitative approach using a literature study method on Ministry of Religious Affairs policies, curriculum guidelines, and relevant research findings. The results show that Kurikulum Cinta has strong philosophical, theological, and pedagogical foundations and is aligned with the Profil Pelajar Pancasila and the Profil Pelajar Rahmatan lil ‘Alamin. The implementation of Kurikulum Cinta in madrasah can be realized through intracurricular and co-curricular learning and the Projek Penguatan Profil Pelajar, thereby contributing to the formation of students who are religious, moderate, tolerant, and of noble character, as well as strengthening religious moderation within the context of Islamic education in Indonesia.